2017
DOI: 10.1016/j.knee.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Poor expectations of knee replacement benefit are associated with modifiable psychological factors and influence the decision to have surgery: A cross-sectional and longitudinal study of a community-based sample

Abstract: Objective Total knee arthroplasty (TKA) is a highly effective surgery, but is underutilized by some patient groups. This study determined factors associated with a person’s expectations with respect to pain and walking function following a TKA procedure, should they elect to undergo a TKA. Methods A total of 3542 people were studied with or at risk of knee osteoarthritis and enrolled in the community-based Osteoarthritis Initiative (OAI). Multivariable logistic regression analyses identified demographic, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
2
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 49 publications
1
15
2
4
Order By: Relevance
“…The present study found no relation between preoperative knee pain or function scores and expectations. These findings reflect results from previous reports, where no relation of preoperative pain 9,30,31 and function scores 9,[30][31][32] with the height of expectations is described. Given the known strong relationship between pre-and postoperative pain and function scores, these findings question the realism of patient expectations.…”
Section: Discussionsupporting
confidence: 90%
“…The present study found no relation between preoperative knee pain or function scores and expectations. These findings reflect results from previous reports, where no relation of preoperative pain 9,30,31 and function scores 9,[30][31][32] with the height of expectations is described. Given the known strong relationship between pre-and postoperative pain and function scores, these findings question the realism of patient expectations.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, given that this is the first study to explore preoperative expectations in such an expansive group of knee surgery patients, we believe that the findings here can help identify possible new predictors of expectations in knee surgery. Whereas we did not find associations between expectations and sex or race, other studies have identified male sex 35 and non-African American race 36 as predictors of greater preoperative expectations in patients undergoing total hip and knee arthroplasty, respectively. Regarding function and general health, previous studies have revealed that patients with worse preoperative hip-specific and overall function had greater expectations of total hip arthroplasty, 35 and that patients with worse preoperative function and general health had greater expectations of total shoulder arthroplasty.…”
Section: Discussioncontrasting
confidence: 99%
“…Racial and ethnic differences in pain expectations have been documented in several studies, largely indicating that poorer pain expectations are experienced by minority patients. For example, several studies have demonstrated that, compared with white patients, black or African-American patients have worse pain expectations from joint replacement surgery [118][119][120][121] and that these differences in expectations account for the race differences in willingness to undergo these surgical procedures [119,121]. Although most of the literature examining race differences in pain expectations has been conducted for joint arthroplasty, an additional study has examined race differences in pain management expectations in the emergency department.…”
Section: Expectationsmentioning
confidence: 99%